Compensation! Is It the Key to Improving Employee Performance and Commitment in the VUCA Era? - Wijaya, Muhammad Adhimawan; Hudiyah, Dewi; Putrie, R. Augia; Falahhuddin, A. (Kompartemen : Jurnal Ilmiah Akuntansi, 2025)
The era of volatility, uncertainty, complexity, and ambiguity (VUCA) and the post-COVID-19 pandemic impact have posed significant challenges for organizations in managing human resources. This research aims to explore how compensation systems, employee well-being, organizational commitment, and individual performance in the manufacturing sector in West Java are affected by a quantitative study using a cross-sectional survey design with 303 respondents out of 500 manufacturing industry employees. Data collection was conducted through questionnaires using a Likert scale and analyzed using Structural Equation Modeling (SEM). The unique finding of this study is that the direct impact of compensation on individual performance is relatively small, but the mediating effect through employee well-being becomes more significant. This research provides empirical contributions that compensation is not merely a mechanism of financial transactions, but a strategic instrument in building a sustainable work ecosystem, in line with the SDGs goals. The main conclusion underscores the importance for organizations to integrate fair compensation strategies with efforts to enhance employee well-being and commitment for sustainable competitiveness.